HUERTIC: una propuesta educativoambiental apoyada en el ABPr para fortalecer valores ambientales y hábitos de vida saludable (2023)
The garden is an excellent tool to convert educational institutions into places that allow students experiences about their natural environment, understand the interactionwith the environment, put into practice values and habits of care; Interesting experiences for the development of fundamental skills for life. This project has great knowledge about the need that students present to strengthen environmental values and healthy habits intheINEM Educational Institution located in Monteria, for which its objective is to value "Huer-tic" an environmental educational proposal supported by learning based in project as axis of articulation for the strengthening of environmental values and healthy lifestylehabits. This research is presented under a qualitative - hermeneutic approach using techniques such as participant observation, focus group interview, then three phases of analysis, of great relevance during the process where the proper description and interpretation of the previous knowledge of knowledge was carried out through the process. atlas ti software, the implementation of knowledge that was carried out in the school garden supported by project-based learning and the use of ICT, as well as the contrasting of knowledge with satisfactory results where students recognize simplistic knowledge in addition to the basic ones that they had at first compared with the knowledge through lived experience that manages to lead them to reflection and decision- making related to environmental values and healthy lifestyle habits.